If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(c + -6) = 10 + -2c Reorder the terms: 3(-6 + c) = 10 + -2c (-6 * 3 + c * 3) = 10 + -2c (-18 + 3c) = 10 + -2c Solving -18 + 3c = 10 + -2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2c' to each side of the equation. -18 + 3c + 2c = 10 + -2c + 2c Combine like terms: 3c + 2c = 5c -18 + 5c = 10 + -2c + 2c Combine like terms: -2c + 2c = 0 -18 + 5c = 10 + 0 -18 + 5c = 10 Add '18' to each side of the equation. -18 + 18 + 5c = 10 + 18 Combine like terms: -18 + 18 = 0 0 + 5c = 10 + 18 5c = 10 + 18 Combine like terms: 10 + 18 = 28 5c = 28 Divide each side by '5'. c = 5.6 Simplifying c = 5.6
| 10z-6(3z+4)=5(2z+(3z+4)-22) | | 4(a+9)=4a+x | | 4(a+9)=4a+36 | | 3x+11=83-6x | | 2t^2-9t-5=0 | | 4x^2-5x+12=8x+2 | | 5x+18=14x-54 | | x^2+19x+30=8x+2 | | x^2-7x+22=10 | | 8x-7=4x+5 | | 3(x+2)-4(x-1)=6 | | 6x+35=8x+13 | | 5(4x-3(x+4))=8x-3 | | 123-4x=32x+23 | | 10-7x=82-21x | | -33-10x=9x+24 | | 2x+14=-76-7x | | 1+5x=45+x | | 4a-4+a+24=6a+20-4a | | 6a-12-8-6a= | | 2(x+3)=4(2x-9) | | -13x+3x-2=5-5x+23 | | (-13x)+3x-2=5-5x+23 | | 5x-3(-10)=15 | | 5x-3(0)=15 | | 5(0)-3x=15 | | x=-10(0)+2 | | 5(p+3)-6(p-4)=30 | | 5Y+2X=12 | | 5(m-4)+3m=24 | | 9x^2-5x+11=0 | | 2x-(9x+2)=11-7x |